Educating for Sustainability : connecting lifestyle to the SDGs of the 2030 Agenda, on Instagram - Gusmão, Paola Pires; Pedroso , Marcela Carlini; Nascimento, Ana Paula Branco do (Technical and Scientific Journal Green Cities, 2025)
SUMMARYObjective – This study investigates how Instagram can be used to promote awareness of the Sustainable Development Goals (SDGs), focusing on targets 11.7, 13.3, and 4.7, which address urban sustainability, climate action, and education. The research assesses the impact of social media in disseminating information on sustainable habits and healthy lifestyles.Methodology – The study combined a literature review, social media management, and practical actions in urban gardens, resulting in weekly publications on the @ods.sustentabilidade profile. Content was organized into carousels, educational posts, and videos, and the impact was assessed through engagement metrics, reflecting the initiative's interest and reach.Originality/relevance – The study highlights Instagram as an effective tool for environmental education and social mobilization for sustainability. The analysis of content formats revealed that video posts had the highest engagement, while carousels on reports and academic texts generated less interaction.Results – The profile reached 730 followers, with 71.2% being women and 96% from Brazil. The combination of digital and local actions, such as events at Horta das Flores and Universidade São Judas Tadeu, proved effective in promoting sustainable practices and environmental education. Integrating social media with in-person initiatives expanded the educational impact.Theoretical/methodological contributions – The research reinforces the importance of adapting digital communication to target audiences, exploring the potential of visual and interactive content to engage different age groups. The study also proposes strategies to improve the use of social media in scientific dissemination and sustainability promotion.Social and environmental contributions – Instagram has proven to be a powerful medium for raising public awareness about the SDGs, encouraging behavioral changes, and promoting greater engagement with environmental issues. The research contributes to the debate on the digitalization of environmental education and its applicability to the 2030 Agenda.
Keywords: Lifestyle; Green Spaces; Sustainable Cities; SDGs